The old motel mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (New York : Scholastic, 1992)
Someone is trying to put Aunt Jane's motel out of business, but the Alden children aren't going to let that happen.
Keywords: Hotels -- Fiction; Bars (Drinking establishments) -- Fiction; Taverns (Inns) -- Fiction; Boxcar children (Fictitious characters) -- Fiction; Orphans -- Fiction; Families -- Fiction; Brothers and sisters -- Fiction; Mystery and detective stories; Mystery fiction